2020
DOI: 10.1002/anie.202012503
|View full text |Cite
|
Sign up to set email alerts
|

A Radical Approach to Making Unnatural Amino Acids: Conversion of C−S Bonds in Cysteine Derivatives into C−C Bonds

Abstract: Here we report a general approach to make unnatural amino acids from readily available cysteine derivatives. This method capitalizes on an intramolecular radical substitution process that generates alkyl radicals through CÀS cleavage. The resulting alkyl radicals partook in diverse CÀC bond forming events. These reactions proceed under mild, photocatalytic conditions at room temperature, and can be performed open to air. The utility of these transformations is further demonstrated in the straightforward synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…We have also shown that sulfides bearing a fluorinated aromatic group can be used to generate alkyl radicals [4] . Recently, a derivatization strategy based on the conversion of the thiol group by means of an iodine (III) regent followed by photoredox initiated radical relay process was reported [5,6] …”
Section: Methodsmentioning
confidence: 99%
“…We have also shown that sulfides bearing a fluorinated aromatic group can be used to generate alkyl radicals [4] . Recently, a derivatization strategy based on the conversion of the thiol group by means of an iodine (III) regent followed by photoredox initiated radical relay process was reported [5,6] …”
Section: Methodsmentioning
confidence: 99%
“…Zhang and Niu established a unique synthesis of unnatural amino acids via the defluoroalkylation of -trifluoromethyl alkenes 77, in which enantiopure gem-difluoroallylated amino acids 108 can be obtained from cysteine derivatives 107 (Scheme 18). 30 First, they used a 2′-iodo-[1,1′biphenyl]-2-yl (oIB) group to develop S-protected cysteines. The oIB group plays a vital role in the generation of the key radical intermediate 112 from cysteine derivatives 107.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…The reaction is not sensitive to the substitution pattern, and substrates with para , ortho , meta -substitution were all viable, giving the desired products in 60–82% yields ( 4a – 4h ). In contrast, the electronic property of the substituent exhibits a big impact, and alkenes with a para -electron withdrawing group afforded no desired products (see the mechanistic discussion), which is consistent with previous reports . In addition, a disubstituted substrate and a bicyclic arene (naphthalene) were readily converted to the corresponding gem -difluoroalkenes 4i and 4j .…”
mentioning
confidence: 95%
“…In particular, we were interested in whether glycosyl radicals could react with α-trifluoromethyl arylalkenes via this reaction pathway to afford gem -difluoroalkene-containing C -alkyl glycosides (Scheme b). Though the reaction of alkyl radicals to α-trifluoromethyl alkenes has been realized by Molander and others, the application of glycosyl radicals in such reactions is hitherto unknown, possibly due to challenges associated with the competitive oxidation or reduction of glycosyl radicals (e.g., to oxocarbeniums). As part of our ongoing project in the synthesis of C -glycosides, we report herein the successful application of glycosyl radicals in an RPC process for the synthesis of C -alkyl glycosides via a photomediated defluorinative gem -difluoroallylation reaction, employing readily available glycosyl bromides as glycosyl radical precursors.…”
mentioning
confidence: 99%